Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1088/0305-4470/28/13/027
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Lie-Backlund symmetry and reduction of evolution equations

Abstract: We suggest a generalization of the notion of invariance of a given partial differential equation with respect to Lie-Bäcklund vector field. Such generalization proves to be effective and enables us to construct principally new Ansätze reducing evolution-type equations to several ordinary differential equations. In the framework of the said generalization we obtain principally new reductions of a number of nonlinear heat conductivity equations u t = u xx + F (u, u x ) with poor Lie symmetry and obtain their exa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
163
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(166 citation statements)
references
References 13 publications
(33 reference statements)
1
163
0
2
Order By: Relevance
“…On the other hand, η 1 depends on u n , and η 2 depends on v n . Hence, (22) holds only for γ = 0, which yields nonlinear determining equation (16). In analogy with the discussion above, we can derive another nonlinear determining equation (17) if DC (3) is compatible with the system (4).…”
Section: Linear Determining Equations For the DC (3) And Clbs (5) Of mentioning
confidence: 83%
“…On the other hand, η 1 depends on u n , and η 2 depends on v n . Hence, (22) holds only for γ = 0, which yields nonlinear determining equation (16). In analogy with the discussion above, we can derive another nonlinear determining equation (17) if DC (3) is compatible with the system (4).…”
Section: Linear Determining Equations For the DC (3) And Clbs (5) Of mentioning
confidence: 83%
“…Fokas and Liu [23] and Zhdanov [58] independently introduced the method of generalised conditional symmetries, i.e., conditional Lie-Bäcklund symmetries. In [44] it was shown that the heirequations can retrieve all the conditional Lie-Bäcklund symmetries found by Zhdanov.…”
Section: Heir-equations and Nonclassical Symmetriesmentioning
confidence: 99%
“…Since 1969, there have been several generalisations of the classical Lie group method for symmetry reductions, such as the non-classical method (Bluman and Cole, 1969), and the method of generalised conditional symmetries (Fokas and Liu, 1994;Zhdanov, 1995). These generalisations were made in an effort to obtain a wider class of symmetries which will lead to new solutions not obtainable via the classical method (see e.g.…”
Section: Introductionmentioning
confidence: 99%